An Ethnobotanical Study of Medicinal Plants in the Greek Islands of North Aegean Region - Axiotis, Evangelos; Halabalaki, Maria; Skaltsounis, Leandros A. (Frontiers in Pharmacology, 2018)
Greek islands of the North Aegean Region are a group of 9 inhabited islands (Lemnos, Agios Efstratios, Lesvos, Chios, Psara, Oinousses, Samos, Ikaria and Fourni) in the northern part of the Aegean Sea, close to Asia Minor. Each island of this region can be considered as an autonomous unit in terms of culture and biodiversity. Therefore, we tried to evaluate the status of the traditional uses of medicinal plants in this remote Greek region. Endemic and endangered species such as Sideritis sipylea Boiss., Origanum sipyleum L., Thymus sipyleus Boiss., Pistacia lentiscus L., Verbascum ikaricum Murb., are still used by natives to treat different ailments. Moreover, the use of some species for the ailment of specific diseases has been reported for the first time. About 109 wild plant species of medicinal importance from 52 families, their uses for therapeutic purposes and galenic preparations by local medical doctors and pharmacists are reported. Information included comes primarily by informants and from literature sources. The information was collected through semi-structured interviews with 200 informants (100 men and 100 women). In addition, informant consensus factor (FIC) and UV value were calculated for the medicinal plants of the current study related with the diseases treated. This research confirms the importance of the medicinal plants and their use in traditional medicine for this region. This ethnopharmacological survey is a fundamental step for the preservation of the local knowledge both for further scientific research and for the protection of endangered and endemic medicinal plants